Magnesium transport in Salmonella typhimurium: expression of cloned genes for three distinct Mg2+ transport systems. - Snavely, M D (1989)
In Salmonella typhimurium, the corA, mgtA, and mgtB loci are involved in active transport of Mg2+ (S. P. Hmiel, M. D. Snavely, C. G. Miller, and M. E. Maguire, J. Bacteriol. 168:1444-1450, 1988; S. P. Hmiel, M. D. Snavely, J. B. Florer, M. E. Maguire, and C. G. Miller, J. Bacteriol. 171:4742-4751, 1989). In this study, the gene products coded for by the corA, mgtA, and mgtB genes were identified by using plasmid expression in Escherichia coli maxicells. Complementation was assessed by introducing plasmids into a Mg2+-dependent corA mgtA mgtB strain and determining the ability of the plasmid to restore growth on medium without a Mg2+ supplement. Complementing plasmids containing corA expressed a 42-kilodalton (kDa) protein. This protein was not expressed by plasmids containing insertions or deletions that eliminated complementation. A plasmid containing mgtA expressed 37- and 91-kDa gene products. Data obtained with subclones and insertions in this plasmid indicated that plasmids expressing only the 91-kDa polypeptide complemented; plasmids that did not express this protein did not complement regardless of whether they expressed the 37-kDa protein. Plasmids carrying mgtB expressed a single protein of 102 kDa whose presence or absence correlated with the ability of the plasmid to complement the Mg2+-dependent triple mutant. Fractionation of labeled maxicells demonstrated that the 42-kDa corA, the 91-kDa mgtA, and the 102-kDa mgtB gene products are all tightly associated with the membrane, a location consistent with involvement in a transport process. These data provide further support the for existence of three distinct systems for Mg2+ transport in S. typhimurium.